Harrison's cardiovascular medicine - 4 0 16; 1900-1978. Loscalzo, Joseph.;Harrison, Tinsley Randolph; 5 (New York : McGraw-Hill Medical, 2010)
A clinical companion, providing an overview of the cardiovascular system, and covering the diagnosis of cardiovascular disorders, heart rhythm disturbances, disorders of the heart, and disorders of the vasculature, with cardiovascular atlases, illustrations, charts, tables, and review questions and answers.
Derived from Harrison's principles of internal medicine, 17th edition--P. facing t.p.
Includes bibliographical references and index.
Adult;Adult.
Keywords: 2 -- 0; 6; Diseases.;Diseases. -- Cardiology.;Cardiovascular system;Cardiovascular Diseases.;Cardiology.;Heart diseases.;Cardiovascular system; 20; 2